STUDY OF C-REACTIVE PROTEIN AND SOME SMALL ANTIOXIDANT MOLECULE LEVELS IN CORONARY ARTERY DISEASE (CAD) - Kadom, Abbas J; AbduAllah, Zainab N (Al-Nahrain Journal of Science, 2018)
Coronary artery disease (CAD) is the most common type of heart disease. It’s the leading causeof death in the developed countries and other parts of the world. The aim of this study was toevaluate antioxidant status (vitamin E, vitamin C and bilirubin) and CRP in 50 patients with (CAD)(Age range: 40 -55 years) and in (40) healthy subjects.The status of antioxidants in serum as represented by bilirubin levels decreased significantly(p<0.01) in the conditions of coronary artery disease (CAD), than their controls, also we evaluatedin this study the concentration of vitamin E and vitamin C in coronary artery disease. Patients with(CAD) showed significantly (p<0.05) lower vitamins concentrations than controls.Furthermore, we assessed the levels of CRP in patients with coronary artery disease comparedwith healthy. CRP levels were significantly higher (p<0.05) in patients compared with healthysubjects.